Experimental Conclusions of the Online Inter-University Creativity, Responsibility, and Entrepreneurship Course Implementation - Barbara Hegyi (MDPI AG, 2023)
The implementation experiences of a new asynchronous online inter-university creativity course-titled "Creativity, responsibility, and entrepreneurship" will be presented through the lens of the course designer. Aside from introducing the identified challenges of how the regular on-site courses can be adjusted to the needs of remote education, with the aim to reach a high completion rate, the main focus remains the introduction of the different level abilities of the students in relation to social responsibility. The unique patterns of positioning the course among its internal and external competitors are created from the combination of theoretical and methodological approaches while also considering the special attitudes of the prospective Eastern European entrepreneur and social responsibility as a distinctive character. Since there was no evidence from the students on how positive social impact as a value in entrepreneurship can be ensured through online courses, the analysis of this potential effect could rely on multiple data sources from a questionnaire, answers to a quiz, and targeted analysis of the final assignments. The aim to improve new iterations call for qualitative data collection. The experimental consequences can guide the prospective course designer through the most important steps of establishing a new online course that leverages the uncommon approach that social responsibility can be an unmissable factor in the competition.